Fusion of technology with language learning: blog community - Nadzrah Abu Bakar,; Hafizah Latif,; Azizah Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper reports findings of an innovative teaching and learning tool which utilizes the weblogs or blogs to increase and widen the ESL learners’ learning opportunities. It firstly reports on the implementation process of the online blogs community as a learning instrument in a tertiary-level ESL classroom. Secondly, it highlights the learners’ feedback being a part of the online blogging community in order to help them enhance their mastery of the English language. The study which involved a select group of low proficiency learners in one Malaysian university utilized online blog discussion activities, interviews and reflection journals as data collection tools. An online blogging community was created and students participated in the group discussion for a duration of one semester. Qualitative analyses of the blog discussion content, interviews and students’ reflection journals conclusively indicate that online blogging community activities, if done in an organized and structured manner, can widen students’ learning opportunities beyond the physical classroom and provide a fresh and effective learning environment for the ESL learners to improve their command of the target language.